The Influence of Religiosity on Academic Achievement with Resilience as An Intervening Variable - Noer Hidayah; Munawaroh Munawaroh (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to examine (1) whether there is a direct influence of religiosity on resilience at MTsN 7 Nganjuk, (2) whether there is a direct influence of resilience on academic achievement at MTsN 7 Nganjuk, (3) whether there is a direct influence of religiosity on academic achievement at MTsN 7 Nganjuk. This research is a descriptive-correlational quantitative study. Data analysis was performed using the path analysis statistical method. The population of the study comprised seventh-grade students at MTsN 7 Nganjuk, with a sample size of 61 students. The results of the study indicate that (1) there is a direct influence of the religiosity variable on the resilience variable at MTsN 7 Nganjuk, (2) there is no direct influence of resilience on the academic achievement variable at MTsN 7 Nganjuk, and (3) there is a direct influence of the religiosity variable on the academic achievement variable at MTsN 7 Nganjuk. Resilience, as an essential asset for students in facing life, can be developed by enhancing their religiosity values. Therefore, the school can design programs or activities oriented towards increasing students' religiosity. This research can be further developed in subsequent studies by incorporating other variables such as learning motivation, learning interest, academic culture, family environment, and school environment, among others.